Determinant Factors Related to Family Utilization of Health Services - Bisepta Prayogi; Khairir Rizani; Ferry Fadli Fratama (Journal of Ners and Midwifery, 2023)
Health is one of the important elements in human life, so the utilization of health services is an important factor in determining health. The utilization of health services has been recommended by the World Health Organization (WHO) as a primary health concept. However, many people do not take advantage of existing healthcare facilities. The purpose of this research was to determine the factors related to the utilization of health services by families. The research method used an analytic observational research design/analytic survey with a cross-sectional approach. The sampling technique used simple random sampling with a total sample of 61 respondents. Bivariate analysis to determine the relationship of each factor was the chi-square test. The results showed that there was no relationship between age and family utilization of health services (p>0.05), there was a relationship between education level and family utilization of health services (p<0.05), there was no relationship between employment status and health service utilization by the family (p>0.05), and there was no relationship between distance (access) and utilization of health services by the family (p>0.05). In this way, families can take advantage of the nearest health service when they are sick so they can find out what disease they are suffering from and get the correct treatment/care